Oblékám Se, Tedy Jsem. Aneb Je Skutečně. - Horáková, Jana.; ProQuest (firma) (Olomouc : Univerzita Palackeho v Olomouci, 2021)
This book tries to find out whether the statement ""Clothes make the man"" is true. Although it is a popular phrase, no one in the field of science and research has yet been able to unequivocally confirm or refute it. For this purpose, the author used a theoretical analysis of historical and contemporary concepts dealing with the relationship between personality and clothing. The book is divided into several parts. First, it deals with the definition of human personality.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books